Becoming a feminist methodologist while researching sexual violence support services - Whittingdale, E (Wiley, 2021)
This article contends that feminist methodologies offer rich and diverse insights for the production of socio-legal knowledge. Recognizing the pioneering work of early feminist methodologists, it explores three key issues that feminist methodologies bring into sharp relief: a push beyond the scientific method, reflexivity, and reciprocity. Drawing upon a case study relating to the long-elided voices and narratives of English sexual violence support workers, the article goes on to discuss the process of applying feminist methodologies in practice. It frames engaging with feminist methodologies during empirical work as a continuous process of becoming, a rigorous project of critical reflection undergirded by the challenges of translating feminist theory into practice. The process of becoming a feminist methodologist is explored here as an evolving and messy labour of commitments, apprehensions, and realizations, and as a way of doing research that recognizes the impossibility of unstitching ourselves from the claims to knowledge that we make.